Preliminary Assessment of Hematopoietic Cell Kinase Gene Expression in Wistar Rats Fed SAMPEA-11 and SAMPEA 20T Diets - Stephen Dio Titus; Salisu Muhammed; Priscila Benjamin; Achilus Francis; Samuel Gadzama Ishaya; Christian Nelson; Kennedy Banja Samuel; Shuaibu M. Bala (Polytechnic Journal)
Dietary factors play a crucial role in modulating immune responses and inflammatory processes. This study investigates the expression of the hematopoietic cell kinase (HCK) gene in Wistar rats fed exclusively with two novel cowpea cultivars, SAMPEA-11 and SAMPEA 20T, to evaluate their potential immunomodulatory effects. The experiment employed a randomized controlled design with six Wistar rats divided into three groups: SAMPEA-11, SAMPEA 20T, and a control group fed a standard diet. Gene expression analysis was performed using real-time quantitative PCR (qPCR), with GAPDH serving as the reference gene for normalization. The results demonstrated significant upregulation of HCK gene expression in rats fed with SAMPEA-11 and SAMPEA 20T compared to the control group. SAMPEA-11 exhibited the highest expression fold change (38.6394), followed by SAMPEA 20T (3.7542), indicating a strong activation of HCK expression. The DDCt values further confirmed this trend, showing the greatest upregulation in SAMPEA-11 (¡5.272) and a moderate increase in SAMPEA 20T (¡1.9085). Statistical analysis revealed a strong inverse correlation between DDCt and expression fold change (r ¼¡0.955, p ¼ 0.191), aligning with expected qPCR trends. Also, regression analysis indicated that DDCt was a strong predictor of expression levels (R2 ¼ 0.913). These f indings suggest that the consumption of SAMPEA-11 and SAMPEA 20T influences immune-related gene expression, potentially impacting immune cell signaling and inflammatory responses. The observed variations between the two cowpea cultivars highlight the need for further investigation into their bioactive components and mechanistic pathways underlying HCK gene regulation. This study contributes to the growing body of knowledge on the dietary modulation of immune function and underscores the potential health benefits of SAMPEA-11 and SAMPEA 20T in immune regulation.